(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, considering the influence of human behavior on heroin abuse, we establish a mathematical model to describe the spread of heroin. When the basic reproduction number is less than one, the heroin-free abuse equilibrium point is globally asymptotically stable. When the basic reproduction number is greater than one, the model has a unique heroin abuse equilibrium point which is globally asymptotically stable, and the heroin-free abuse equilibrium point is unstable. Finally, based on the partial rank correlation coefficients (PRCCs) and numerical simulations, the dynamic behavior of the model is further revealed. Our results show that human behavior can reduce the heroin abuse level.